An Analysis of The Perspectives of Aristotle And Imam Al Shatibi on Legal Justice - Parid; Mahendra, Sandya; Nur Milla (Universitas Muhammadiyah Surakarta, 2024)
The issue of justice in society is still a matter of debate among academics, working practitioners and ordinary people. The objectives of this research include (1) To explain the concept of justice in the views of Aristotle and Imam Asy Syatibi; (2) To conduct a comparative analysis between Aristotle's and Imam Asy Syatibi's concepts of justice. The research method used is qualitative research using a philosophical and comparative approach. The results of this research explain that Aristotle's view of justice is a grant of equal rights but not equality. Aristotle differentiates equal rights from proportional rights. In his view, Aristotle divided it into three types, namely, commutative, distributive and corrective justice. Meanwhile, in Imam Asy-Syatibi's view, the concept of justice is part of the maqashid sharia framework, which is the goal of religion to create benefits for all mankind. Ash-Syatibi conceptualizes justice in the Kulliyat al-Khamsah principle with the following priorities: maintenance of religion, soul, lineage, reason, and property which are summarized in three levels, namely dharuriyyat, Hajiyyat, and Tahsinniyat, Aristotle and Imam Asy-Syatibi have similarities and differences which is pretty basic. The similarity of the concept of justice in Aristotle and Imam Asy-Syatibi lies in the desire that justice can lead to the welfare of society and create a civilized, moral personality in society. Meanwhile, the difference between Aristotle's and Imam Asy-Syatibi's concepts of justice lies in the philosophical approach, justice criteria and final goals.